2017
DOI: 10.1007/s10900-017-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

Purchases Made with a Fruit and Vegetable Voucher in a Rural Mexican-Heritage Community

Abstract: Recent recommendations for US food assistance programs are intended to ensure foods provided through these programs help households consume a varied, healthful diet. From a policy viewpoint, it is important to examine the impact of economic incentives to purchase healthy foods across subpopulations, particularly low-income Latinos, who comprise 40% of the WIC program nationwide. Our aim was to determine how rural, Mexican-heritage households (N = 227) residing in California's Central Valley distributed fruit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies have observed higher rates of diet-related health problems in populations with lower consumption of fruits and vegetables (22,23) . The use of fruit and vegetable voucher programmes, which assist individuals and families at risk of diet-related health problems to purchase healthy foods, demonstrate trends towards increased consumption of fruits and vegetables among those receiving the intervention (24)(25)(26) . Such programmes have typically targeted urban, low-income populations and have not previously been widely developed within a tribal community.…”
mentioning
confidence: 99%
“…Indeed, previous studies have observed higher rates of diet-related health problems in populations with lower consumption of fruits and vegetables (22,23) . The use of fruit and vegetable voucher programmes, which assist individuals and families at risk of diet-related health problems to purchase healthy foods, demonstrate trends towards increased consumption of fruits and vegetables among those receiving the intervention (24)(25)(26) . Such programmes have typically targeted urban, low-income populations and have not previously been widely developed within a tribal community.…”
mentioning
confidence: 99%